2018
DOI: 10.1101/465070
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The multi-speed genome ofFusarium oxysporumreveals association of histone modifications with sequence divergence and footprints of past horizontal chromosome transfer events

Abstract: 21Fusarium oxysporum is an economically important pathogen causing wilting or rotting 22 disease symptoms in a large number of crops. It is proposed to have a structured, 23 "two-speed" genome: i.e. regions containing genes involved in pathogenicity cluster 42 genes evolving at similar rates could increase evolvability. 43 44

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
72
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(84 citation statements)
references
References 92 publications
(112 reference statements)
9
72
3
Order By: Relevance
“…This contrasts with the organization of TE-rich regions in Z. tritici, which are enriched with both heterochromatin modifications (43). The situation in Lmb is also different from that of Fusarium oxysporum in which most TE sequences are embedded in H3K27me3-domains (66). We confirmed that, as in most Eukaryotes, H3K4me2-domains are associated with expressed genes while H3K9me3-and H3K27me3-domains are associated with silent genes.…”
Section: Discussionsupporting
confidence: 47%
“…This contrasts with the organization of TE-rich regions in Z. tritici, which are enriched with both heterochromatin modifications (43). The situation in Lmb is also different from that of Fusarium oxysporum in which most TE sequences are embedded in H3K27me3-domains (66). We confirmed that, as in most Eukaryotes, H3K4me2-domains are associated with expressed genes while H3K9me3-and H3K27me3-domains are associated with silent genes.…”
Section: Discussionsupporting
confidence: 47%
“…The 5' 9.8-kb subtelomere of contig 22 was at 99. .96% identity to the 5' subtelomeres of contigs 9,15,32,86,87, to a region of contig 107 from positions 9.9 to 19.7 kb, all in forward orientation, and to the 3' subtelomere of contig 30 in reverse orientation.…”
Section: Resultsmentioning
confidence: 98%
“…A DNA helicase regulates mutually exclusive expression of virulence genes in the subtelomeres of Plasmodium falciparum via heterochromatin alteration ). In the asexual pathogen Fusarium oxysporum, SM/pathogenicity gene clusters (facultative heterochromatin) are marked by histone H3 lysine 27 trimethylation (H3K27me3), while euchromatin is marked by histone H3 lysine 4 dimethylation (H3K4me2) (Fokkens et al 2018). Because subtelomeres contain repetitive DNA, their DNA sequences are difficult to reconstruct by genome assembly programs, so they are sparsely represented in databases of whole genome sequence data (Wu et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the loss frequency of lineage-specific chromosomes was estimated to be approximately 1 in 35,000 in spores in a liquid culture. Surprisingly, core chromosome 12 in Fol4287 can also be lost but at a very low rate of 1 in 190,000 spores (5,66). In Zymoseptoria tritici , spontaneous accessory chromosome loss rate was much higher with chromosome loss in 2 to >50% of cells during four weeks of incubation (65).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that repetitive elements can lead to intra- or inter-chromosome homologous recombination, resulting in deletions or translocations (67). It has also been shown that in some fungi the facultative heterochromatin mark H3K27me3 is present in both the subtelomeric regions of the core chromosomes and accessory chromosomes (12,66). This difference in histone modification compared to the core chromosomes may play a role in the difference in chromosome stability (66,68).…”
Section: Discussionmentioning
confidence: 99%